Label-free target identification in drug discovery via phenotypic screening. (June 2019) - Park, Hankum; Ha, Jaeyoung; Park, Seung Bum
Graphical abstract: Abstract : Phenotypic screening has demonstrated its advantage in the discovery of first-in-class therapeutics, whereas target-based screening has showed strength for follower drugs. Owing to the unbiased nature of phenotypic screening, novel druggable proteins can be uncovered by target identification. Chemical label-free target identification methods can eliminate the functionalization step of an original bioactive compound. Herein, we summarize recent advances in the development of label-free target identification methods, which are based on changes in protein stability against proteolysis, and chemical and thermal denaturation. Owing to the increasing application of shift in thermal stability for protein analysis in live cells and tissues, we mainly focus on the cellular stability shift assay and its proteome-wide application for target identification.